Citizenship Education in Malawi: A critique in defence of maximal citizenship - Divala, Joseph Jinja (My University, 2006)
This dissertation analyses assumptions about citizenship education in Malawi since the reintroduction of multiparty democracy in 1993 and reveals a minimalist conception of citizenship. It asserts that Malawi’s historical and traditional context require concerted efforts towards participatory citizenship if democracy is to be strengthened and protected. Central to the discussion are conceptual distinctions between minimal and maximal citizenship alongside a discussion of concepts of freedom, human rights and development, which can be attributed to minimal and maximal conceptions of citizenship. The dissertation argues that deliberative and participatory forms of democracy, with their parallel notions of contestatory and republican freedoms and rights, are more attuned to creating an active and strong citizenship while at the same time developing a positive relationship between democratic participation and participation in local and national development, a relationship which representative approaches in Malawi seemingly disavow.
Faculty of Humanities, School of Education, Master of Education Dissertation
Keywords: Education; Citizenship; Democracy; Representation; Participation; Malawi